Embedded fracture model in numerical simulation of the fluid flow and geo-mechanics using Generalized Multiscale Finite Element Method - Tyrylgin, Aleksei; Vasilyeva, Maria; Chung, Eric T. (Journal of physics. Conference series, 2019)
In this work, we consider a pororelasticity problem in fractured porous media. Mathematical model contains a coupled system of equations for pressure and displacements, for which we use an embedded fracture model. The fine grid approximation is constructed based on the finite volume approximation for the pressure in fractured media and finite element method for the displacements. Multiscale approximation is developed using a structured coarse grid and is based on the Generalized Multiscale Finite Element Method for pressures and displacements. The performance of the method is tested using a two-dimensional model problem with different number of the multiscale basis functions.